RANCANG BANGUN SISTEM ANTARMUKA OTOMATISASI MODEL BENDUNG GERAK - Didik Purwantoro, Pramudiyanto (Universitas Negeri Yogyakarta, 2011)
The dam is always identified as the shelter of water (water storage) which is used to satisfy the needs of human life. However, the dam holds in its development can also be used for agricultural irrigation systems in line with the development of agriculture. Up to this point, the dam holds still utilized in accordance with the basic concept that for the purposes of everyday, the need for agriculture (irrigation), energy (electricity), flood control, and so on. Then for ease in learning and understanding the characteristics of a dam holds then created a model that approximates the actual dam holds that aims to be able to better understand the symptoms that occur at a dam holds. The purpose of this research is to be able to create a system interface and information systems that can support a model dam holds motion. The resulting Model can then be used as a medium of learning technology application in the dam Hydraulics courses.Design of a system of an interface automation a model of weir motion it consists of design of hardware and software. Hardware design includes a series of sensors and driver circuit motor SRF02 stepper. Data obtained in this study was analyzed using the Chauvenette Criterion Method. This method of data are invalidate and tends to produce outlayer interpretation is not good. The test results showed that the value of the resulting data transducer SRF02, the equation of y = -0.698x + 8.2062 with coefficients of correlation value 0.9705. This shows that the transducer used to have a good liniear equation of high water on the overflow that is measurable.The test showed that the stepper motor has been able to move in accordance with orders. From the test results can be seen that the software has been created can be run and hardware are made to work according to have commands that are present in the software. So it can be inferred that the system that has been created can work well.